KAJIAN HISTORIS TERHADAP WABAH PADA MASA NABI MUHAMMAD SAW (571-632 M) - Novita Nurlaeli Handayani (JSI: Jurnal Sejarah Islam, 2022)
At the time of the Prophet Muhammad SAW has experienced various kinds of challenges, one of which is a plague. The emergence of the Plague made the impact of transmission very fast and deadly. However, Prophet Muhammad SAW was able to minimize the transmission of the plague by providing a policy. This study uses the "Challenge and Response" theory proposed by Arnold J. ToynBee. While the method used is a historical research method. The results from this study are plague that occurred during the time of the Prophet Muhammad in the period 571-632 AD, namely smallpox plague, fever plague and kusta/leprosy plague. These plagues are caused by animals and natural conditions as well as the social conditions of the community which are still not good. The symptoms caused by each plague are also different, with very fast transmission affecting friends and the surrounding community. However, the policies given by the Prophet Muhammad SAW can minimize the transmission and spread of the plague.